Study of an eco-friendly enzymatic dehairing of skins and hides using alkaline protease - Abdullah Sidek, Yasmin Suraya (2020)
This study was aimed to provide an eco-friendly alternative to dehairing of hides by replacing the chemical with the usage of the protease. The leather industry is one of the biggest contributor of the pollution. The use of chemical like sodium sulfide caused the wastewater effluents to contain high level BOD, COD, and TDS. To overcome this issue, an alternative method has been proposed to replace chemical in dehairing the hides in the leather industry. In this research, three types of treatment were done in order to compare the efficiency of the dehairing treatment. The treatments are conventional, single enzyme and enzyme assisted. For the conventional treatment, the hides were soaked in 5% calcium oxide and 2% sodium sulfide and incubated at 37 °C for 24 hours at 120 rpm. Meanwhile, for the enzyme assisted treatment, the hides were soaked in 5% Calcium oxide for 6h and then soaked in 10%, 20%, 30% and 40% of protease for 24 hours at 37°C at 120 rpm. Lastly, for the single enzyme treatment, the hides were soaked in 10%, 20%, 30% and 40% of protease for 24 hours at 37 oC at 120 rpm. The results were that hides that were treated with conventional treatment and single enzyme of 20% concentration has the highest % area yield which is 100% and they are the most efficient among all other treatments. The physical wastewater analysis indicates that conventional treatment’s wastewater is bad for the environment. In conclusion, single enzyme treatment’s wastewater does not do any harm to the environment and it is also very efficient in dehairing of the hides.